MicroRNA-200c plays an oncogenic role in nasopharyngeal carcinoma by targeting PTEN - Zhen-Zhen Zhang (Tumor Biology, 2017)
Recent studies suggested that microRNA-200 family microRNAs play critical roles in cancer initiation and metastasis. The underlying mechanism remained elusive. In this study, we show that microRNA-200c is upregulated in nasopharyngeal carcinoma cells. Manipulation of microRNA-200c levels affected cell growth, migration, and invasion in nasopharyngeal carcinoma cell lines. Furthermore, PTEN was identified as a direct target of microRNA-200c. Overexpression of PTEN resulted in similar effects to those of anti-microRNA-200c transfection. In vivo suppression of microRNA-200c level reduced tumor growth in mice. Overall, our data suggest that microRNA-200c plays an oncogenic role in nasopharyngeal carcinoma by targeting PTEN.